Decision-Making in Family Planning: Women, Planned Children and Contraceptive Methods in Muslim Family - Nurhayati, Nurhayati; Hayati, Fitri; Siregar, Putra Apriadi; Hasibuan, Reni Ria Armayani; Naldo, Jufri; Japakiya, Ismail Lutfi; Affendi, Hazrul (Mazahib, 2024)
Family planning programmes are not optimal for Muslim women; this is inseparable from the view that contraception is controversial in Islamic teachings. This study aims to examine the influence of the ideal number of children, the role of husbands, the desired last child, and the type of contraception in Muslim women of childbearing age from the perspective of Islam and health. This study used data from the 2017 IDHS in Aceh, West Sumatra, Riau, West Java, Central Java, and East Java on 5797 Muslim women from January to December 2022. The results of this study showed a significant association between the ideal number of boys (p<0.001; PR = 1.332), number of daughters (p<0.001; PR = 1.289), husbands who decide (p=0.004), and contraceptive types (p<0.001; PR = 1.205) with family planning use. The family planning use is influenced by factors such as gender preference, joint decision-making, and the type of contraceptive used. Modern contraceptives are more effective and reliable, suggesting a trend toward modern methods for family planning.